2008
DOI: 10.1103/physreve.78.031131
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-random-number generators and the square site percolation threshold

Abstract: A select collection of pseudorandom number generators is applied to a Monte Carlo study of the two dimensional square site percolation model. A generator suitable for high precision calculations is identified from an application specific test of randomness. After extended computation and analysis, an ostensibly reliable value of pc = 0.59274598(4) is obtained for the percolation threshold.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 51 publications
4
33
0
1
Order By: Relevance
“…33 This value is much smaller than the percolation threshold of impurities on the nearest-neighbor square lattice model 0.41. 19,34 The pair breaking effect induced by the disorder is also relevant to the T c decrease. Indeed, as can be seen from Fig.…”
Section: Discussionmentioning
confidence: 98%
“…33 This value is much smaller than the percolation threshold of impurities on the nearest-neighbor square lattice model 0.41. 19,34 The pair breaking effect induced by the disorder is also relevant to the T c decrease. Indeed, as can be seen from Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have also shown that the percolation threshold is dependent of conductive fillers morphology (size, shape and the aspect ratio) [24][25][26][27] . The distribution of scattered points is not a real situation of electrically conductive composites; however, this method of particles distribution has been widely adopted for comparison with known percolation threshold values [28][29][30][31] .…”
Section: Verification Of Simulator For Scattered Pointsmentioning
confidence: 99%
“…By increasing the probability of black cells, infinite clusters more often appear, as predicted also by the percolation theory. Also, the results of the algorithm are in accordance with site percolation thresholds in the square lattice ( [16,24]). …”
Section: Lemma 3 the Algorithm Has Linear Time Complexitymentioning
confidence: 57%